Results of pericardiectomy for constrictive pericarditis Single-center experience - AKALIN, FİGEN; ARSAN, SİNAN; BİRKAN, YAŞAR (URBAN & VOGEL, 2017)
We evaluated our early and late outcomes after pericardiectomy in patients with constrictive pericarditis (CP). We retrospectively reviewed 31 patients who underwent pericardiectomy for CP from 1997 to 2015. Their mean age was 49.2 +/- 18.5 years and 74.2 % of them were male. The vast majority had severe functional impairment (NYHA class III-IV) with a mean duration of symptoms of 14.2 +/- 10.1 months. Early mortality was 9.7 %: n = 3; multiorgan failure (MOF) in 1, respiratory failure in 1, and left heart failure in 1. Preoperative systolic pulmonary artery pressure over 60 mmHg (p = 0.038, odds ratio [OR] = 0.12) and postoperative low cardiac output syndrome (p = 0.005, OR = 13.5) were significant predictors of early mortality in univariate analysis. Mean follow-up time was 57.8 +/- 61.9 months (4-216 months). Late mortality was 6.8 % (2/28 patients) and the cause was MOF secondary to end-stage right heart failure. In Kaplan-Meier analyses, actuarial (including early mortality) and event-free survival rates were 83.9 and 51.1 % at 216 months, respectively. At the end of follow-up, the majority of patients (23/26, 92.9 %) were in good functional status (NYHA class I-II). There were fewer patients under diuretic therapy in the postoperative than in the preoperative period; however, the difference was not statistically significant (12/31 vs. 4/26, p = 0.76). There was no significant difference between the preoperative and follow-up tricuspid annular plane systolic excursion values (15.5 +/- 2.2 and 16.6 +/- 2.2 mm, respectively, p = 0.088). Left ventricular systolic function was preserved in all patients postoperatively. Although early mortality after pericardiectomy remains high, the procedure provides significant improvement in functional status in the long term.
Keywords: Constrictive pericarditis; Pericardiectomy; Tuberculous pericarditis; Functional capacity; Mortality and survival; TUBERCULOUS PERICARDITIS; MANAGEMENT; PREDICTORS; IMPACT; PYOPERICARDIUM; DIAGNOSIS; SURVIVAL; OUTCOMES; CHOICE; RISKS